Analysis of piled foundations with piles rigidly jointed to pile caps under coupled support stiffness. Issue 2 (2nd April 2016) - Law, C W; Cheng, Y M
ABSTRACT: A discussion is presented on analyses of piled foundations with the pile caps simulated as beam or slab structures supported on piles simulated as elastic springs carrying support stiffnesses with various degrees of freedom. In this paper, the shortcoming of applying only settlement, translational and rotational stiffnesses to the elastic springs for piles rigidly jointed to the pile cap in an integrated analysis of the lateral shears and out-of-plane loads for a piled foundation are explained. These shortcomings lie in the failure of this approach to account for the effects on the out-of-plane actions in the pile cap and the subsequent axial loads on the piles due to lateral translations, which can create moments at the pile heads. However, with the insertion of "coupled support stiffnesses" which relates the pile head translations to moments into the stiffness matrix of the pile cap, accurate analytical results can be obtained. As most commercial software does not allow for the input of such stiffnesses, the paper also discusses an approach that can arrive at the close analytical results and yet remain on the conservative side of estimation.